Hubungan antara densitas mikrovaskular dan limfoplasmasitik dengan metastasis kelenjar getah bening inguinal pada pasien karsinoma penis di RSUP Sanglah, Bali, Indonesia - Silvester Kristian Taopan; Anak Agung Gde Oka; I Gde Raka Widiana; I Wayan Juli Sumadi (DiscoverSys Inc., 2021)
Background: Carcinoma is the most common malignancy that occurs in penile tissue. Most of the metastasis of penile carcinoma is lymphogenic to the nearest lymph node. Metastasis is a significant prognosis factor in reflecting the outcome of penile carcinoma patients. To begin a process of metastasis requires the formation of new blood vessels (angiogenesis) and infiltration of mononuclear cells. Both of these can be assessed through micro vessel density and lymphoplasmacytic. This study aims to determine the relationship between microvascular and lymphoplasmic density with inguinal lymph node metastases in penile carcinoma patients at Sanglah General Hospital, Bali, Indonesia.Methods: This research is an analytic cross-sectional study. Data collection was carried out from the patient's Medical Record during January 2014 - December 2018. From 40 samples of penectomy surgery the micro vessel Density and lymphoplasmacytic readings were first stained with staining of hematoxylin eosin by anatomic pathologist. Cut-off point microvessel density and lymphoplasmacytic is taken by calculating the mean and standard deviation. Bivariate analysis with Chi Square Test and multivariate analysis using logistic regression tests were used for statistical analysis. Data were analyzed using SPSS version 20 for Windows.Results: From the Bivariate Analysis it was found that there was a significant relationship between Micro-vessel Density and Metastasis to the inguinal lymph node (P=0.019) and there was a significant relationship between lymphoplasmacytic and metastasis to the inguinal lymph node (P=0.005). The Multivariate Analysis confirms that microvessel density, lymphoplasmacytic and history of phimosis are significantly related to the occurrence of metastasis to inguinal lymph node in penile carcinoma patients (p=0.040).Conclusion: There were significant relationships between Micro vessel Density and Lymphoplasmacytic density with metastasis to inguinal lymph nodes in patients with penile SCC. A history of phimosis was proved to be a dominant risk factor. Latar Belakang: Karsinoma merupakan keganasan tersering yang terjadi pada jaringan penis. Sebagian besar metastasis karsinoma penis bersifat limfogen menuju Kelenjar Getah Bening (KGB) terdekat. Untuk memulai suatu proses metastasis diperlukan pembentukan pembuluh darah baru (angiogenesis) dan infiltrasi sel mononuklear. Kedua hal tersebut bisa dinilai melalui densitas mikrovaskuler dan limfoplasmositik. Penelitian ini bertujuan untuk mengetahui hubungan antara densitas mikrovaskular dan limfoplasmositik dengan metastasis kelenjar getah bening inguinal pada pasien karsinoma penis di RSUP Sanglah, Bali, Indonesia Metode: Penelitian ini merupakan penelitian potong lintang analitik. Pengambilan data dilaksanakan dari Rekam Medis pasien selama Januari 2014 – Desember 2018. Dari 40 sampel Operasi Penektomi dilakukan pembacaan densitas mikrovaskuler dan limfoplasmositik yang telah lebih dulu diberikan pewarnaan Hematoxylin Eosin oleh ahli patologi anatomi. Titik potong densitas mikrovaskuler dan limfoplasmositik diambil dengan cara menghitung rerata dan standar deviasi. Analisis bivariat dengan Uji Chi-Square dan analisis multivariat dengan menggunakan uji regresi logistik digunakan untuk analisis statistik. Data dianalisis dengan SPSS versi 20 untuk Windows.Hasil: Analisis bivariat didapatkan hubungan yang bermakna antara Densitas Mikrovaskuler dengan metastasis ke KGB Inguinal (p=0,019) dan terdapat hubungan yang bermakna antara limfoplasmositik dengan metastasis ke KGB inguinal (p=0,005). Analisis multivariat menegaskan bahwa densitas mikrovaskuler, limfoplasmositik dan riwayat fimosis berhubungan secara bermakna dengan terjadinya metastasis ke KGB Inguinal pada pasien karsinoma penis (p=0,040).Simpulan: Adanya hubungan antara Densitas Mikrovaskular dan Limfoplasmositik dengan metastasis ke KGB inguinal pada pasien dengan KSS penis. Riwayat fimosis merupakan faktor resiko dominan.